Calling All Activists to the Capitol - Oluseyi Adegbola (Journal of Public Interest Communications)
The role of elected officials as focal point of activism is well understood. However, activism by politicians is underexplored. Drawing on the collective action framing literature and the protest paradigm, this study examines the strategic messaging employed by elected officials in their efforts to rally media attention and act as oppositional publics able to influence other citizens to action. Centered on the case of congresswoman, Cori Bush, who mobilized support for an eviction moratorium during the Covid-19 pandemic, this study reveals patterns of strategic messaging used to mobilize key publics in support of the moratorium and highlights the potential use of activism to elevate elected officials’ public profile. Theoretical and practical implications are discussed.